Virtual reality and artificial intelligence applied to consumer experience: a scenario-based approach - Fino, Fábia Patrícia Fidalgo (2018)
Emerging technologies like Virtual Reality (VR) and Artificial Intelligence (AI) have been receiving much attention in the Marketing context as a new way to attract customers and enrich their experiences with brands. This study aimed to research the current state of these technologies in Business and discuss the extent to which experiences using Virtual Reality and Artificial Intelligence may impact a customer experience in three different points of the customer journey: pre-purchase, purchase, and post- purchase stage. An online survey was constructed to measure the effectiveness of VR and AI on a scenario-based approach, along three consumer behaviours in the customer journey – brand associations (pre-purchase stage), purchase intention (purchase stage) and brand loyalty (post-purchase stage). From a sample of 302 respondents, the results suggest that these technologies represent valuable opportunities in Marketing. Overall, the results revealed that the type of experiences addressed in this paper are more prone to instil action (purchase stage) than to build brand associations (pre-purchase stage) or brand loyalty (post-purchase stage). An in-depth analysis of these results manifested interesting outcomes, suggesting several managerial on how to apply these technologies in an integrated marketing communication (IMC) plan.